Experimental study on hybridoma cells agglutination test for diagnosis of schistosomiasis japonica in mice - Liu, Wenqi; Li, Yong-long; Ruppel, Andreas (Zhong guo ji sheng chong xue yu ji sheng chong bing za zhi, 2003)
OBJECTIVE: To detect the infection of Schistosoma japonicum in mice with a novel test based on agglutination of hybridoma cells and to study the mechanism of the hybridoma cells agglutination. METHODS: The procedure was developed with a murine cell line H226 producing a monoclonal antibody specific to schistosome 31/32 kDa antigen and sera collected from mice infected with different numbers (10, 30, 50) of S. japonicum cercariae in different period. Immunofluorescent test was carried out with the hybridoma cells and schistosome-infected sera. RESULTS: The circulating antigen was detected by the test as early as 2 weeks after a heavy infection and all mice showed positive results in the test by 5 weeks after infection. The titers of antigen rose along with the time post infection, and the titers of sera from heavy infection were statistically higher than that from the mice receiving a lower number of cercariae. Specific yellowish green fluorescence appeared on the membrane of the hybridoma cells; no signal was detected inside. CONCLUSION: Hybridoma cell agglutination test (HCAT) may become useful to diagnose schistosomiasis.
Gesehen am 14.04.2021